Public Policy for Women: The State, Income Security and Labour Market Issues - Prentice, Susan (Labour / Le Travail, 2010)
The article reviews the book, "Public Policy for Women: The State, Income Security and Labour Market Issues," edited by Marjorie Griffin Cohen and Jane Pulkingham.
Keywords: BOOKS – Reviews; COHEN; Marjorie Griffin; Canada; EMPLOYMENT policy; Nonfiction; PUBLIC Policy for Women: The State; Income Security & Labour Market Issues (Book); PULKINGHAM; Jane